Evaluation of university sports culture in the new era, based on philosophical context - Ming Lei; Hong Ma (Trans/Form/Ação)
University sports culture is an important component of the national cultural system. It is the crystallization of material and spiritual civilization in university sports, as well as the precipitation of sports culture and sports philosophy. However, in the new era, university sports culture presents problems, such as valuing intelligence over physical fitness, lacking in sports culture concepts, and separating spirit and material. In university education, more attention is often paid to academic and intellectual development, while sports and physical exercise are lightly regarded. In fact, university sports culture often focuses only on physical education and sports events, while ignoring the development of other aspects, resulting in an imbalance in the whole sports culture system. The insufficient investment of the school in sports facilities and equipment leads to a lack of necessary material support for students to engage in physical exercise. At the same time, the students’ understanding and pursuit of sports often remain on the surface, lacking in the pursuit of the spirit of the deep-seated. In review of university sports culture, dialectical materialism can be used to analyze the connection among the social background, development trend and mutual influence of sports culture. The perspective of social constructivism can also be used to explore the social construction process of sports culture, all participants’ roles and interactions, and the significance and influence of sports culture in society. Therefore, in order to better solve the problems existing in university sports culture, promote the rapid development of university sports culture in the new era, enhance the confidence of campus sports culture and build a strong sports culture, this article used dialectical materialism method to analyze the current situation of university sports. It explained the relationship between philosophy and sports culture from a philosophical perspective, as well as the current problems in sports culture. Finally, it used the method of social constructivism to explain it from different perspectives. Finally, through the social constructivism method, it examined the university sports culture in the new era and, dialectically, analyzed the forms, functions, reconstruction paths and future thinking of university sports culture. Research has found that the sports culture of universities, in the new era, plays an important role in cultural, educational, and political aspects. The reconstruction and future development of university sports culture, in the new era, need to combine Eastern and Western cultures, inherit excellent traditional culture and achieve innovative development of sports culture.